Effectiveness of Empowering School Teachers to Screen Refractive Errors in School Going Children in the Rural Area of Vadodara, Gujarat - Patel, Divyangkumar N; Kathad, Manish M; Jay, Pujani; Rathod, Anshi; Rawal, Arpit; Rathod, Jay (National Journal of Community Medicine, 2018)
Introduction: Does the empowering school teachers in reflectory error screening reduced the burden of preventable cause of blind- ness? In most of the schools, eye check-up is done yearly at a time of school health week program. If we can able to empower school teacher to diagnose with appropriate technology of refractive error measurement we can reduced the encumbrance of refractive error. Does it easy as it sounds? Methodology: the study was non-randomised control trial done among school going children of 5 to 8 years of age done in rural area of Vadodara district. New model (screening of refractory er- ror by school teachers) was compared with standard model (screening of refractory error by medical doctors) to assure validity and reliability of screening model for identifying reflective error. Results: Kappa statistics was found 0.4482, which indicates weak agreement on comparison of both models. Sensitivity of new mod- el (31.25%) was also low as compared with standard model. Conclusion: Applicability of new model (refractive error screening by trained teachers) is not proven, as validity and reliability of new model was poor.